Penentuan Kondisi Optimum Proses Ekstraksi Uranium dan Torium dari Terak II Timah dengan Metode Pelindian Asam Sulfat dan Solvent Extraction Trioctylamine (TOA) - Anggraini, Mutia; Nawawi, Fuad Wafa; Widana, Kurnia Setiawan (EKSPLORIUM, 2019)
Tin slag II is a by-product of the second stage of tin smelting. The tin slag II contains high economic value elements in the form of radioactive elements (uranium and thorium) and rare earth elements. These elements can be utilized if they are separated from each other. The process of separating radioactive elements and rare earth elements has been carried out by leaching sulfuric acid method. The results of this process are residue containing rare earth elements and filtrates containing radioactive elements in the form of uranium and thorium sulfate. Research related to the separation of uranium and thorium sulfate in tin slag processing is only slightly published. This paper aims to determine the effectiveness of the uranium and thorium separating process by the solvent extraction method using trioctylamine (TOA). The solvent extraction process is carried out by varying the concentration of TOA used, comparison of the aqueous and organic phase (A/O) and variations in extraction time. In this study, the optimum conditions for the process were obtained at 4% of TOA concentration, 1 : 1 of A/O ratio, and mixing time of aqueous and organic phase for 2 minutes. In this condition, uranium and thorium which extracted were 67% and 0.84% respectively.